(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
Computer-guided navigation has emerged as one of the most significant technological advancements in modern implant dentistry, fundamentally transforming the planning and execution of dental implantation procedures. The integration of three-dimensional imaging, cone-beam computed tomography, digital treatment planning software, and dynamic navigation systems has considerably improved surgical precision, implant positioning accuracy, and long-term clinical outcomes. Contemporary research demonstrates that computer-assisted implant placement minimizes deviations between planned and actual implant positions while reducing surgical trauma and postoperative complications. The technology enables clinicians to evaluate anatomical structures with greater precision, identify potential risks before surgery, and develop individualized treatment strategies based on patient-specific anatomical characteristics. Furthermore, guided navigation contributes to improved prosthetic outcomes by facilitating prosthetically driven implant placement and optimizing functional and aesthetic rehabilitation. Statistical analyses from recent multicenter studies indicate implant survival rates exceeding 95–98% when advanced navigation protocols are employed. This article examines the scientific principles, clinical applications, technological developments, and evidence-based advantages of computer-guided navigation systems in dental implantation, emphasizing their role in improving treatment predictability, safety, and long-term success.